Does music training enhance working memory performance? Findings from a quasi-experimental longitudinal study. (March 2014) - Roden, Ingo; Grube, Dietmar; Bongard, Stephan; Kreutz, Gunter
Instrumental music training has been shown to enhance cognitive processing beyond general intelligence. We examined this assumption with regard to working memory performance in primary school-aged children ( N = 50; 7–8 years of age) within a longitudinal study design. Half of the children participated in an extended music education program with 45 minutes of weekly instrumental music training, while the other half received extended natural science training. Each child completed a computerized test battery three times over a period of 18 months. The battery included seven subtests, which address the central executive, the phonological loop and the visuospatial sketchpad components of Baddeley's working memory model. Socio-economic background and basic cognitive functions were assessed for each participant and used as covariates in subsequent analyses of variance (ANOVAs). Significant group by time interactions were found for phonological loop and central executive subtests, indicating a superior developmental course in children with music training compared to the control group. These results confirm previous findings concerning music training and cognitive performance. It is suggested that children receiving music training benefit specifically in those aspects of cognitive functioning that are strongly related to auditory information processing.